Comparison of the of Operative Treatment and Sclerotherapy Injection in the Management of Hemorrhoids: A Meta-Analysis of Randomized Controlled Trials - Wiyardhani, Laras; Sander, Tara; Wibriansyah, Akbar (Syntax Corporation Indonesia, 2025)
Rubber-band ligation (RBL) and sclerotherapy are the two most widely used office-based interventions for symptomatic haemorrhoidal disease, yet their comparative benefits remain uncertain. This systematic review and meta-analysis evaluated the relative efficacy and safety of sclerotherapy versus operative treatments (primarily RBL and excisional procedures). The primary objective of this systematic review and meta-analysis was to evaluate the relative efficacy and safety of sclerotherapy versus operative treatments (primarily RBL and excisional procedures) in the management of hemorrhoidal disease. Treatment success was 78.2% in operative arms (701/896) versus 74.1% with sclerotherapy (665/897); pooled RR = 1.03 (95% CI 0.91–1.17; I² = 85%), indicating non-inferiority of sclerotherapy. Recurrence in two trials (n = 302) showed lower recurrence after sclerotherapy (12.9%) than after operative treatment (28.4%); RR = 2.22 (95% CI 1.37–3.58; I² = 0%). Pain in three trials (n = 335) reported a higher risk of significant pain following operative procedures (RR = 1.17, 95% CI 1.02–1.34; I² = 60%) and greater mean pain intensity (SMD = 0.96, 95% CI 0.22–1.71; I² = 89%). Sclerotherapy achieves comparable short-term symptom control to operative treatments while offering superior durability and a more favorable pain profile. Given its minimal invasiveness and ease of repetition, modern sclerotherapy should be considered a first-line option for grade I–III haemorrhoids. High between-study heterogeneity underscores the need for standardized protocols and longer follow-up.